Social Media Usage for Learning English Language - Saidatul Hanim (Randwick International of Education and Linguistics Science Journal, 2021)
The reason of this consider was to decide the sorts of social media utilized by fourth-semester students of the Department of English Literature, Universitas Negeri Medan, for learning English. The analyst utilized clear subjective inquire about, and the information were collected using a questionnaire. The participants were 50 students of the Department of English Letters, Muria Kudus University. The results showed that the social media used by students to learn English were YouTube (94%), Instagram (72%), WhatsApp (62%), Twitter (32), Facebook (30%), Line (10%), Google (2%), TikTok (2%).